Rekonstruksi etika finansial islam: membandingkan paradigma bank dan asuransi syariah vs konvensional di era ekonomi digital - yani, indra (Maliki Interdisciplinary Journal, 2025)
This article discusses the reconstruction of Islamic financial ethics, covering topics related to definitions, characteristics and traits, principles, legal foundations, as well as the comparison between Islamic banks and insurance vs. Islamic and conventional insurance. By using the library research method aimed at collecting various data, such as scientific articles, journals, and books relevant to the discussion, it is hoped that, as a Muslim, one must understand the basics or concepts of banks and insurance that use either the shariah or conventional system.